IFLA President's Meeting 2015 Istanbul - (:unkn) unknown (TURKISH LIBRARIANS ASSOC, 2015)
International Federation of Library Associations and Institutions (IFLA) organizing presidency meetings in connection with the developments for library and information services by the themes defined. Eighth Meeting of Presidency has been organized in cooperation with ANKOS, Turkish Librarians' Association (TLA), Istanbul BilgiUniversity in Istanbul with the invited speakers and attendants from various disciplines. The meeting titled in The Art of Transformation of Libraries was carried out in the framework organized under the five major themes. These titles are: IFLA Trend Report and Lyon Declaration Transforming Technologies: Opportunities and Threats Legal Regulations and the Impact on Information Technologies Transformation in Public Libraries Knowledge Economy in All Aspects This study will be referred to the content of the topics covered at the meeting. Various libraries around the world and have recently considered plans, projects discussed these issues with examples for our Turkish colleagues working in the field of library and information services, and it has hoped that to be seminal.
Keywords: IFLA; IFLA President's Meeting 2015; non governmental organizations; NGO